(untitled) (UNED Research Journal, 2018)
There are more than 189 slums in Costa Rica Metropolitan Area. The National Financial System for Housing has the eradication slums program. This financial model invests economic resources on those kind of settlements to improve infrastructure condition through construction processes. For this research, three slums assisted by PEPT were chosen to assess environmental and social conditions: Los Cuadros, Tirrases and Miramar. These settlements include five public spaces destined for parks, recreation, sports and urban areas, as well as a controlling space that is not managed by PEPT located in Los Cuadros. Environmental and social conditions were evaluated before and after the economic intervention to analyze indicators variation associated with water, soil, air, urban elements, waste, society and communal organization. A qualification system was created with similar structure used by the National Environmental Technical Secretariat (SETENA due to its acronym in Spanish) to evaluate the influence on construction projects. Four of five public spaces showed environmental improvements related to urban elements, lighting, water management, floor covering and waste management, and one of them showed social improvements related to occupants practices and customs. They are statistically significant after resources investment. The controlling space did not show representative statistical changes in the environmental characteristics assessed. Finally, the economic investment in public spaces located in slums offers not only social but environmental benefits.